A simple way to fine tune the redox potentials of cobalt ions encapsulated in nitrogen doped graphene molecular catalysts for the oxygen evolution reaction. Issue 91 (28th October 2016) - Wang, Jiong; Lin, Wen-Feng; Shi, Yi; Wang, Huai-Song; Rong, Lian-Qing; Xia, Xing-Hua
Abstract : A simple approach to fine-tuning the redox potential of Co 2+ ions encapsulated in nitrogen doped graphene (NG) has been proposed. We found that the redox potential determines the oxygen evolution reaction activity of the catalyst. Abstract : Co 2+ ions encapsulated in nitrogen doped graphene were applied as an oxygen evolution catalyst. Their redox potentials were tuned using different counter anions as liable ligands, and the redox potential related catalytic rates were explored. It was proposed that the electron density of Co 2+ ions was a general descriptor for activity.